Intellectual Property Rights Perspective: The Effort in Providing of the World Public Health Rights Due to Covid-19 - Maydrawati, Tri Rusti (Fakultas Hukum Universitas Hang Tuah, 2024)
The existence of Covid-19 has made many countries strive to save their citizens. The competition between developed and developing countries for vaccine and drug supplies has created its own tension. Vaccine supplies for developed countries have exceeded the needs of their citizens, while for developing countries there are limitations, compared to the number of citizens. This is very contrary to human rights, especially in accessing drugs and vaccines. The purpose of this study is to determine the ideal form of cooperation agreements and arrangements to overcome the limitations of Covid-19 drugs and vaccines for the fulfilment of the right to health from an Intellectual Property Rights perspective. secondly to find out the efforts that can be made by developing countries to save their citizens. The results and discussion are first, the state's obligation to save citizens for the fulfilment of the right to health, based on the principles of justice and expediency. Second, the fulfilment of citizens' health rights based on the TRIPs Agreement, the Doha Declaration, and the Patent Law. Furthermore, the third is the ideal concept in regulating international cooperation in the context of equitable distribution of the covid 19 vaccine by seeking the cooperation of pharmaceutical companies in developed countries with pharmaceutical companies owned by developing countries in overcoming this global pandemic. And this cooperation must be followed by all members who participate in the WTO agreement.